EVALUATION OF TRIGLYCERIDES LEVELS IN SERUM AND TEARS OF OBESE AND NON-OBESE NORMAL ADULT HUMANS AND ITS EFFECTS ON PUPILLARY RESPONSE - Hanif, Sommaya; Fatima, Sadia; Nazli, Rubina; Ullah, Noor; Zeb, Falak; Usama (Journal of Ayub Medical College Abbottabad, 2022)
Background: Triglycerides are a type of storage fat present in serum of both normal and obese individuals. Triglycerides are normally present in human tears. The presence of qualitative fats in the tears affect the pupillary response to the external light stimulus which is measured through portable field dark adaptometer (PFDA) device. The current study was conducted to evaluate the levels of triglycerides in serum and tears of obese and non-obese humans and its relationship with pupillary response. Methods: This descriptive cross-sectional study was conducted at Institute of Basic Medical Sciences, Khyber Medical University, Peshawar. A total of 500 participants were recruited out of which only 50 qualified for the study as per inclusion criteria. Out of these 50, 25 (50%) were obese and 25 (50%) were non-obese. Serum triglycerides were measured by using Micro lab 300 biochemistry analyzer, while thin layer chromatography was used to detect triglycerides in tear samples. Results: Triglycerides were detected only in tears of obese individuals. No statistically significant difference was observed in the serum levels of triglycerides between the two groups (p=0.849). Conclusion: The presence of triglycerides in tears of obese adults caused a low pupillary response as compared to normal individuals.